The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1124/mol.109.055863
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Determinants in the Pore Region of Sodium Channels Regulate Local Anesthetic Binding

Abstract: The pore of the Na ϩ channel is lined by asymmetric loops formed by the linkers between the fifth and sixth transmembrane segments (S5-S6). We investigated the role of the Nterminal portion (SS1) of the S5-S6 linkers in channel gating and local anesthetic (LA) block using site-directed cysteine mutagenesis of the rat skeletal muscle (Na V 1.4) channel. The mutants examined have variable effects on voltage dependence and kinetics of fast inactivation. Of the cysteine mutants immediately N-terminal to the putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…cationic and sodium-bound electroneutral ligands in the channel. (A) The triethylammonium group of QX-314 is close to the Na III site, the aromatic ring binds between F 4i15 and Y 4i22 , and the ligand also interacts with Q 1p49 and F 3p49 in agreement with mutational data (Yamagishi et al, 2009). (B) The bulky moiety of quinidine fits the hotspot at the Na III site, whereas the hydroxyl group donates an H bond to 3p48 O=C.…”
Section: Bisphenol Asupporting
confidence: 62%
See 1 more Smart Citation
“…cationic and sodium-bound electroneutral ligands in the channel. (A) The triethylammonium group of QX-314 is close to the Na III site, the aromatic ring binds between F 4i15 and Y 4i22 , and the ligand also interacts with Q 1p49 and F 3p49 in agreement with mutational data (Yamagishi et al, 2009). (B) The bulky moiety of quinidine fits the hotspot at the Na III site, whereas the hydroxyl group donates an H bond to 3p48 O=C.…”
Section: Bisphenol Asupporting
confidence: 62%
“…Mutations in the selectivity filter (the DEKA locus) also affect the action, strongly suggesting electrostatic interactions with the selectivity filter (Sunami et al, 1997). More ligand-sensing residues are found at the P-loops (Tsang et al, 2005;Yamagishi et al, 2009), but the data on roles of these residues are fragmental. Thus, mutational studies unambiguously show the ligand-binding region and suggest candidate residues that contribute to receptors of various ligands, but they do not provide a complete picture of the channel interactions with the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…S2C–D). Mutation of a homologous residue in rat Na V 1.4 to cysteine had modest effects on channel function (38), suggesting that the observed change in pore hydrophobicity is critical at this residue.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the same group demonstrated that the drug-specific kinetics of binding to slow inactivated states by lidocaine and bupivacaine closely matched the kinetics of sulfhydryl modification of a cysteine engineered to the outer vestibule ( 58 ). Yamagishi et al ( 59 ) observed that application of external QX314 (a membrane-impermeant quaternary derivative of lidocaine) did not block rNa V 1.4 channels but nevertheless slowed recovery from internal block by QX314, suggesting an allosteric effect of external QX314 binding on recovery from internal block. In the rNa V 1.2 channel a potential interaction between Trp-1716 in the DIV-P-loop (corresponding to Trp-1531 in rNa V 1.4) and Phe-1764 in the DIV-S6 segment (corresponding to Phe-1579 in rNa V 1.4) was recently reported, being closely related to anticonvulsant and/or local anesthetic binding ( 60 ).…”
Section: Discussionmentioning
confidence: 99%